2021
DOI: 10.5501/wjv.v10.i6.312
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 (SARS-CoV-2 infection) in lymphoma patients: A review

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection now has a global resonance and represents a major threat for several patient populations. Observations from initial case series suggested that cancer patients in general might have an unfavorable outcome following coronavirus disease 2019 (COVID-19), due to their underlying conditions and cytotoxic treatments. More recently, data regarding the incidence and clinical evolution of COVID-19 in lymphomas have been reported with the aim to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 71 publications
(51 reference statements)
1
35
0
Order By: Relevance
“…The incidence of COVID-19 was found to be more frequent in acute leukemias (29%), followed by non-Hodgkin’s lymphoma (27%) and Hodgkin’s lymphoma (18%) [ 24 ]. Furthermore, an increase in mortality has been reported in myeloid malignancies (MDS/AML/MPN) than lymphoid neoplasms (NHL/CLL/ALL/MM/HL) (43% vs. 35%) [ 25 , 26 ], which is similar to that seen in our study population. The majority of our study patients were on active treatment and reported a mortality rate of 19.6%, in contrast to 10% among patients on surveillance.…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of COVID-19 was found to be more frequent in acute leukemias (29%), followed by non-Hodgkin’s lymphoma (27%) and Hodgkin’s lymphoma (18%) [ 24 ]. Furthermore, an increase in mortality has been reported in myeloid malignancies (MDS/AML/MPN) than lymphoid neoplasms (NHL/CLL/ALL/MM/HL) (43% vs. 35%) [ 25 , 26 ], which is similar to that seen in our study population. The majority of our study patients were on active treatment and reported a mortality rate of 19.6%, in contrast to 10% among patients on surveillance.…”
Section: Discussionsupporting
confidence: 90%
“…Lymphoma patients are often immunosuppressed by their active disease per se, and lymphodepleting therapies including anti-CD20 monoclonal antibodies, chemotherapy, with targeted agents also leading to an additional immunosuppressive effect. 20 The speed and degree of humoral and cellular immune recovery following prolonged immunosuppression following therapy interruption is unclear. The impact of different therapeutic approaches in patients with COVID-19 remains poorly defined, but active chemotherapy appears to be associated with increased risk of death in cancer patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies showed high rates of COVID-19 severity in patients with B-lymphoid malignancies, but no increase in COVID-19 severity or mortality associated with treatment of B-lymphoid malignancies. However, these studies were smaller than the current study and did not compare outcomes with untreated control populations (11,14,23,24). This is the largest study of patients specifically with B-lymphoid malignancies and COVID-19 to date, with a cohort of 995 of such patients.…”
Section: Discussionmentioning
confidence: 78%